PERILAKU KOLOM KOMPOSIT TABUNG BAJA BERISI BETON NORMAL AKIBAT BEBAN AKSIAL SENTRIS DAN EKSENTRIS - , Desi Putri ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The column is a structural component that is dominant receiving axial loads. The composite column in this review is a steel column which is made from tube or steel pipe and filled with structural concrete. The composite column has resistance to bending, more resistant to erosion and more rigid. The research of cross-sectional circle column is conducted to understand the properties of the behavior of composite columns of normal concrete casted in cylinder steel tube